Prerogative of the President in About the State of Emergency (Comparison of Indonesia with the United States) - Farid Wajdi; Andryan Andryan (International Journal Reglement & Society (IJRS), 2021)
In the 1945 Constitution there are two regulations regarding emergency situations (danger) which are regulated in two articles, namely Article 12 and Article 22. Article 12 of the 1945 Constitution states,